TO STUDY THE FUNCTIONAL AND RADIOLOGICAL OUTCOMES OF ANKLE ARTHRODESIS WITH CORTICOCANCELLOUS SCREW FIXATION VS INTRAMEDULLARY NAILING - SINGH, SUMIT KUMAR; REHNCY, JAGDEEP SINGH; MEHTA, HARRY; BAKSHI, AMANDEEP SINGH (International Journal of Current Pharmaceutical Research, 2024)
Objective: We aimed to evaluate the functional and radiological outcomes of ankle arthrodesis using corticocancellous screw fixation vs intramedullary nailing. Methods: In our study, 22 cases underwent the procedure. This evaluation was performed based on preoperative radiologic data and at postoperative clinical visits at 2 months, 6 months, and 12 mo required postoperatively. Radiologic outcomes were measured by: (1) Rate of union, (2) Rate of adjacent joint arthritis, and (3) Alignment of the ankle joint. Functional outcomes were measured by using the AOFAS score (American Orthopedic Foot and Ankle Society score). The patients' Subjective assessments were done using the Cumberland Ankle Instability Tool (CAIT). Results: The angle between the tibia's long axis and a line parallel to the talus's long axis is determined in the AP projection. The mean angle was 89.6 degrees (85-100 degrees) in the intramedullary nailing group (IMN group) and 91.4 degrees in the corticocancellous screw group (CC screw). The angle between the tibia's long axis and a line that is perpendicular to the talus’s long axis. The mean angle was 40.5 degrees (30-45 degrees) in the IMN group and 41.6 degrees in the CC screw group. The mean AOFAS score (American Orthopedic Foot and Ankle Society score) was 83.25 in the IMN group and 80.5 in the other group. The mean Cumberland Ankle Instability Tool (CAIT) score was 28 in the IMN group and 27.5 in the other group. All the cases showed bony union except one case, the average time taken for the union was 18.5 w in the IMN group and 20.5 w in the CC screw group. Conclusion: According to our study, all of the patients with normal angles between the tibia's long axis and a line perpendicular to the talus's long axis were obtained in the AP projection, and the angle between the tibia's long axis and a line that is perpendicular to the talus’s long axis. These patients also showed better Cumberland Ankle Instability Tool (CAIT) and AOFAS (American Orthopedic Foot and Ankle Society) scores in both comparison groups.